Accuracy of a computerized tomography-guided template-assisted implant placement system: an in vitro study - Horwitz, Jacob; Zuabi, Otman; Machtei, Eli E. (Clinical oral implants research, 2009)
Objectives: To evaluate the accuracy of computer‐assisted 3D planning and implant insertion using computerized tomography (CT). Materials and methods: Nine implants were planned on pre‐operative CTs of six resin models, which were acquired with radiographic templates, using a planning software (E implants). Each resin model contained three pre‐existing control implants (C implants). Radiographic templates were converted into operative guides containing 4.8‐mm‐diameter titanium sleeves. A single set of insertable sleeves was used for consecutively drilling the six models, followed by implant insertion through the guide sleeves. Models were further divided into group A (the first three models) and group B (the last three models). Post‐operative CTs were used to compare implant positions with pre‐operative planned positions. Statistical analysis included the Mann–Whitney U test for E and C implants and the Wilcoxon's signed ranks test for groups A and B. Results: The mean apex depth deviations for E and C implants [0.49 mm±0.36 standard deviation (SD) and 0.32 mm±0.21 SD, respectively], and the mean apex radial deviations (0.63 mm±0.38 SD and 0.49 mm±0.17 SD, respectively) were similar (P>0.05). The mean angulation deviations for E and C implants were 2.17±1.06°SD and 1.33±0.69°SD, P<0.05. E implant deviations of all the parameters in group A were significantly smaller than E implant deviations in group B. Conclusions: Computer‐assisted implant planning and insertion provides good accuracy. Deviations are mainly related to system and reproducibility errors. Multiple use of drills and titanium sleeves significantly reduces system accuracy.